DETAILED STUDY ON THERAPEUTIC PROPERTIES, USES AND PHARMACOLOGICAL APPLICATIONS OF SAFFLOWER (CARTHAMUS TINCTORIUS L.) - Gautam, Sanskriti; Bhagyawant, Sameer S.; Srivastava, Nidhi (International Journal of Ayurveda and Pharma Research, 2015)
Safflower (Carthamus tinctorius L.) belongs to the family Asteraceae. Safflower has been grown mainly for orange-red dye (carthamin) extracted from its flower used in food coloring and flavoring. Safflower seed oil is highly rich in linoleic acid (unsaturated fatty acid) which makes it highly suitable for human consumption. The whole plant of C. tinctorius possesses many pharmacological activities like antifibrosis, antidiabetic, antitumour, anti-inflammatory, hepatoprotective, antihperlipidemic, anticoagulant, and antioxidant activities. Regardless of it numerous uses, this crop is under the category of minor and neglected crop, therefore additional research work is required for its commercialization. The present review critically deals with botanical description, distribution, classification, uses, pharmacological activities and chemical constituents present in safflower.